CULTIVATION OF PUMPKIN CUCURBITA PEPO VARIETIES IN THE SOIL-CLIMATIC CONDITIONS OF KARAKALPAKSTAN - Yeshchanova S. SH.; Panaeva A. N. (Galaxy International Interdisciplinary Research Journal, 2022)
Farming in agrocenoses for many years with the use of various agricultural technologies and chemicals can negatively affect the indicators of soil fertility (composition and reserves of organic matter in the soil, nutrients, acidity of the soil solution, bulk mass, etc.). In the history of mankind, the development of agriculture is one of the factors determining the center of international culture, and it plays an important role in reducing natural landscapes and, in turn, in changing the ecological balance. Ensuring the sustainability and profitability of agricultural production depends on the effective use of all biological resources in the agrocenosis. In agriculture, based on modern agrotechnologies, it is necessary to study the biological and genetic characteristics of varieties suitable for the agro-climatic characteristics of the region. Adaptation of various varieties to local soil and climatic conditions in agriculture, i.e. biologization and ecologization, requires systematic use of natural, biological, man-made, labor and other resources. The balance of agroecology in the agrocenosis is an important factor in the formation of species and varieties of cultivated plants [5,6].